Characterization of carbonate derived carbons through electrochemical impedance spectroscopy. (1st April 2020) - Hughes, Matthew A.; Allen, Jessica A.; Donne, Scott W.
Abstract: Carbons have been produced through the electrolytic reduction of mixed molten carbonate salts at a range of temperatures, current densities, and using a variety of substrates. Variation in the morphological structure of carbons has been observed for carbons deposited at 500–700 °C. In-depth equivalent circuit modelling of the electrochemical impedance spectroscopy response of synthesized and activated carbons has shown mass transfer, inductive effects, and charge transfer effects all contribute to the supercapacitive performance of the examined carbons. Patterns have been highlighted in the inductances of carbons and the implications of this for optimal cycling frequency, cycling window, and synthesis conditions has been highlighted. The electrolyte-electrode interactions between 0.5 M H2 SO4 and the synthesized carbons has been investigated in a manner which may be generalised to analyse other supercapacitive systems, and the electrolyte coverage, porosity, and Mott-Schottky behaviour of the materials have been quantified. High, frequency-dependent, capacitances of up to 160 F g −1 have been obtained for carbons deposited at either low temperature or low current density, and for carbons deposited in binary Li2 CO3 –K2 CO3 eutectics.